Congenital bilateral absence of the vas deferens: the impact of spermatogenesis quality on intracytoplasmic sperm injection outcomes in 108 men. (6th March 2015) - Llabador, M. A.; Pagin, A.; Lefebvre‐Maunoury, C.; Marcelli, F.; Leroy‐Martin, B.; Rigot, J. M.; Mitchell, V.
Summary: In azoospermic men with congenital bilateral absence of the vas deferens (CBAVD), it is not known whether the outcomes of intracytoplasmic sperm injection (ICSI) depend on the quality of testicular spermatogenesis (as determined histopathologically). We retrospectively studied the impact of spermatogenesis quality on ICSI outcomes in 108 azoospermic men with CBAVD consulting in a university hospital's department of andrology and reproductive biology. As part of an ICSI program, sperm samples were obtained from the epididymis [by microsurgical epididymal sperm aspiration (MESA); n  = 47] or the testis [by testicular sperm extraction (TESE); n  = 14] or both (MESA + TESE, n  = 47). In the TESE group (i.e., TESE‐only and MESA + TESE), spermatogenesis was normal in 21 of the 108 men (19.4%) and hypospermatogenesis occurred in 33 (30.5%). The fertilization rate was significantly lower in the hypospermatogenic group than in the normospermatogenesis group (65.6 and 72.9%, respectively; p  =   0.02); this was also true for the embryo cleavage rate (88.6 and 92.1%, respectively; p  =   0.007), and the proportion of embryos with fewer than 30% of enucleate fragments (79.5 and 86.9%, respectively; p  =   0.02). Our study results showed that impaired spermatogenesis had a negative impact on certain early‐stage biological outcomes of ICSI. In CBAVD, male factors are likely to exert a harmful effect on the early stages of embryo development.